Equivalent stabilizing force of the simply supported roof girders including the longitudinal variability of the compression force acting in the restrained chord = Obciążenie imperfekcyjne przegubowo podpartych dźwigarów dachowych z uwzględnieniem wzdłużnej zmienności siły ściskającej w ich stężanym pasie - Biegus, Antoni; Czepiżak, Dariusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In the calculation model of the equivalent stabilizing force qd for bracing system consistent with EN 1993-1-1 it has been conservatively assumed that the member to be restrained is uniformly compressed within its length by an axial force. This assumption is incorrect owing to the actual distribution of the axial force which is non-uniform in the shape of parabola.
Keywords: steel structures; lateral bracing system; equivalent stabilizing force; roof girder; konstrukcje stalowe; stężenia dachowe; obciążenie imperfekcyjne; dźwigar dachowy; stężenie; płatew